György Kurtág three interviews and Ligeti homages - Varga, Bálint András 1941-2019 (Eastman studies in music, 2009)
Uniquely revealing interviews with one of the world's greatest living composers. Gy©rgy Kurt©Łg (b. 1926) is widely regarded as one of the foremost composers in the second half of the twentieth century and the early twenty-first. Born in Romania, he received crucial training in Paris from Olivier Messiaen and Marianne Stein. He was also shaped by his broadening contact there with the music of Webern and such challenging literary works as the plays of Samuel Beckett. After many years in Hungary, teaching at the Budapest Academy of Music,Kurt©Łg settled near Bordeaux with his wife M©Łrta. The two regularly perform duo-recitals of his music. In 2006, his . . . concertante . . . (2003, for violin, viola and orchestra) won the coveted Grawemeyer Award for MusicComposition. This unique set of interviews with Kurt©Łg, alone or with his wife, gives a fascinating insight into the composer's personality, which is marked by shyness but also an unquenchable thirst for impressions of every kind [artistic, natural and human]. The two speak with disarming openness about their lives -- the background against which masterpieces like Messages of the Late Miss R. V. Troussova (1976-80, for soprano and chamber orchestra) or Stele (1994, for orchestra) were written. The analysis of certain of Kurt©Łg's works, especially of . . . concertante . . ., shows the way that his mind works: no system, no dogma, no formulae -- rather, basic human emotions expressed through means that speak directly to the listener's innermost feelings. The Hungarian music publisher B©Łlint Andr©Łs Varga has spent nearly forty years working for and with composers.He has published several books, including extensive interviews with Lutoslawski, Berio, and Xenakis